Efektivitas Cognitive Behavior Therapy (CBT) Terhadap Kecemasan, Stres dan Peningkatan Resiliensi Pada Korban Pascabencana Banjir : Literature Review - Alfriyani, Meyunda; Mustikasari, Mustikasari (Journal of Telenursing (JOTING), 2024)
This research aims to describe Cognitive Behavior Therapy (CBT) for anxiety, stress, and increasing resilience in post-flood disaster victims through a literature study search. The method used is a journal review approach from the Proquest, Science Direct, Pubmed, Scopus databases with the keyword Cognitive Behavior Therapy AND Anxiety, Cognitive Behavior Therapy AND Stress AND Resilience. with inclusion criteria, full paper articles, English, Indonesian, publications in the last 10 years, namely from 2020 to 2024, disaster victims. The results of the research show that of the 10 articles that can be used for literature reviews, CBT is effective in reducing anxiety disorders, stress and increasing resilience. Conclusion Cognitive Behavior Therapy (CBT) is effective in reducing anxiety, stress and increasing resilience in victims of natural disasters who experience anxiety, stress and low resilience. Keywords: Cognitive Behavior Therapy, Anxiety, Stress, Resilience, Post-Flood DisasterVictims.